2020
DOI: 10.1136/bmjopen-2020-037192
|View full text |Cite
|
Sign up to set email alerts
|

Complementary medicine in orthopaedic and trauma surgery: a cross-sectional survey on usage and needs

Abstract: ObjectivesComplementary and alternative medicine (CAM) is frequently used in Western countries within general medicine and internal medicine. Information on the use in orthopaedic and trauma surgery is widely lacking. The aim of this study was to investigate usage and needs regarding CAM for these patients.DesignProspective paper-based, pseudoanonymous, cross-sectional survey.SettingFrom August to December 2018, a questionnaire composed of 17 questions was distributed to all eligible patients.ParticipantsIn-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 18 publications
(24 reference statements)
4
15
1
1
Order By: Relevance
“…Other recent studies reported that up to one-third of patients communicated about their CAM usage with their attending physician. Communication differs between inpatients and outpatients and depends on the attending physician's specialization [4,9,11,[26][27][28]. Kilper et al reported that only 15% of inpatient orthopaedic and trauma patients in Germany indicated their use of CAM [4].…”
Section: Non-communication About Cammentioning
confidence: 99%
See 4 more Smart Citations
“…Other recent studies reported that up to one-third of patients communicated about their CAM usage with their attending physician. Communication differs between inpatients and outpatients and depends on the attending physician's specialization [4,9,11,[26][27][28]. Kilper et al reported that only 15% of inpatient orthopaedic and trauma patients in Germany indicated their use of CAM [4].…”
Section: Non-communication About Cammentioning
confidence: 99%
“…Communication differs between inpatients and outpatients and depends on the attending physician's specialization [4,9,11,[26][27][28]. Kilper et al reported that only 15% of inpatient orthopaedic and trauma patients in Germany indicated their use of CAM [4]. In a Hungarian study, 13% of inpatient surgical patients told their attending physician about their CAM interest [9].…”
Section: Non-communication About Cammentioning
confidence: 99%
See 3 more Smart Citations